A Patient with Arterial Thoracic Outlet Syndrome Relieved by a Calcium Channel Blocker - Benbir Şenel, Gülçin (Cerrahpaşa Medical Journal, 2025)
Cite this article as: Şenel GB. A patient with arterial thoracic outlet syndrome relieved by a calcium channel blocker. Cerrahpaşa Med J 2025, 49, 0073, doi: 10.5152/cjm.2024.24073